Understanding and Overcoming the Challenges Posed by Electrode/Electrolyte Interfaces in Rechargeable Magnesium Batteries - Mizuno, Fuminori; Singh, Nikhilendra; Arthur, Timothy S.; Fanson, Paul T.; Ramanathan, Mayandi; Benmayza, Aadil; Prakash, Jai; Liu, Yi-Sheng; Glans, Per-Anders; Guo, Jinghua (Frontiers in Energy Research, 2014)
Guided by the great achievements of lithium (Li)-ion battery technologies, post Li-ion battery technologies have gained a considerable interest in recent years. Their success would allow us to realize a sustainable society, enabling us to mitigate issues like global warming and resource depletion. Of such technologies, Magnesium (Mg) battery technologies have attracted attention as a high energy-density storage system due to the following advantages: (1) potentially high energy-density derived from a divalent nature, (2) low-cost due to the use of an earth abundant metal, and (3) intrinsic safety aspect attributed to non-dendritic growth of Mg. However, these notable advantages are downplayed by undesirable battery reactions and related phenomena. As a result, there are only a few working rechargeable Mg battery systems. One of the root causes for undesirable behavior is the sluggish diffusion of Mg2+ inside a host lattice. Another root cause is the interfacial reaction at the electrode/electrolyte boundary. For the cathode/electrolyte interface, Mg2+ in the electrolyte needs a solvation-desolvation process prior to diffusion inside the cathode. Apart from the solid electrolyte interface (SEI) formed on the cathode, the divalent nature of Mg should cause kinetically slower solvation-desolvation processes than that of Li-ion systems. This would result in a high charge transfer resistance and a larger overpotential. On the contrary, for the anode/electrolyte interface, the Mg deposition and dissolution process depends on the electrolyte nature and its compatibility with Mg metal. Also, the Mg metal/electrolyte interface tends to change over time, and with operating conditions, suggesting the presence of interfacial phenomena on the Mg metal. Hence, the solvation-desolvation process of Mg has to be considered with a possible SEI. Here, we focus on the anode/electrolyte interface in a Mg battery, and discuss the next steps to improve the battery performance.